Preparation of Wastelage using Poultry Droppings and Wet Rice Straw as a Cattle Feed (Journal of the Bangladesh Agricultural University, 2020)
An experiment was conducted with wet rice straw (WRS) treated with poultry droppings (PD) and molasses to increase the nutritional and preservation quality by ensiling. Five different combination was prepared as T0 (100% WRS), T1 (5% Molasses + 95% WRS), T2 (5% PD+ 5% Molasses+ 90% WRS), T3 (10% PD + 5% Molasses+ 85% WRS) and T4 (15% PD+ 5% Molasses+ 80% WRS). The mixed ingredients were preserved in plastic containers under airtight condition at room temperature. Physical quality, chemical composition, in-vitro organic matter digestibility (IVOMD) and Metabolizable Energy (ME) content at 0, 30, 45, 60 and 90 days were measured and calculated. The physical quality (color, smell, and hardness) of straw improved in PD added treatments till 90 days of ensiling except in T4 where some pungent smell was found after 60 days. The pH value was decreased (P